Contributions of Selected Classroom Factors on Bullying Among Adolescents in Secondary Schools in Kenya. - Nyaga, Milcah Njoki (The International Journal of Humanities & Social Sciences, 2018)
Bullying is a major challenge in secondary schools in Kenya. The vice is practised underground among students thus many students experience high level of bullying without the knowledge of teachers and parents.The study investigated the contributions of classroom factors on bullying among adolescents in secondary schools in Kenya. The study was grounded on Bronfenbrenner’s Ecological theory. A descriptive design was employed. The sample of 320 students was obtained through random sampling and while eight deputy principals were selected from sampled schools. The instruments for data collection were student’s questionnaire, deputy principal’s questionnaire, record analysis and researcher’s observation schedules. The data was analysed through descriptive statistics and Chi- square was used to test for the association between the classroom factors and bullying. The findings revealed that all the classroom factors: general discipline, individuals responsible for discipline, common disciplinary measures, rating of disciplinary measures and counselling services, were significantly associated with bullying.The findings revealed that bullying was very common though it was rarely disclosed to school management. Further, the study observed that the teachers were administering corporal punishment and in most cases the punishment was not proportional to the offence committed. In addition, the guidance and counselling services were not effectively offered in most schools. The study recommended that all teachers should be involved in matters of discipline in schools. Similarly, the disciplinary measures should also be modified in consultation with the students and teachers. The counselling services need to be activated and managed by trained teacher counsellors.
Keywords: Adolescent; Bullying; Classroom; Teacher; Student; Behaviour